Peran Kegiatan “Family Gathering” dalam Membangun Emosi Sosial Penyandang Thalassemia di Banyumas - Faiza, Dinar; Lestari , Diyah Woro Dwi; Suprihatin, Suprihatin; Purwoko, Ari; Aminah, Siti; Rujito, Lantip (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
Thalassemia is a genetic disease that is still a problem in Indonesia. Patients often face emotional problems and difficulties in social relationships. This condition can affect the management and treatment of thalassemia. Family gatherings play an important role in strengthening the support system for thalassemia patients and their families. The collective strength and determination gained from this family gathering helps thalassemia patients and their families face the challenges of this condition head-on, bringing a sense of hope and optimism for the future. Family gathering activities were carried out which were attended by more than 200 patients and their families. Overall, family gatherings focused on strengthening thalassemia families and patients provide an important platform for support, education, and empowerment. Family gatherings increase emotional support, belonging, remove stigma, and motivate to always be better.